2020
DOI: 10.1002/anie.201903391
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Levitation in Chemistry, Materials Science, and Biochemistry

Abstract: All matter has density. The recorded uses of density to characterize matter date back to as early as ca. 250 BC, when Archimedes was believed to have solved “The Puzzle of The King's Crown” using density.[1] Today, measurements of density are used to separate and characterize a range of materials (including cells and organisms), and their chemical and/or physical changes in time and space. This Review describes a density‐based technique—magnetic levitation (which we call “MagLev” for simplicity)—developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 190 publications
1
108
0
Order By: Relevance
“…Since then, principles of magnetic levitation are being used successfully and broadly in different areas of technology and industries [3]. In 1997, Geim performed the diamagnetic levitation of a living organism (frog) in the air at the High Field Magnet Laboratory at Radboud University in Nijmegen, The Netherlands, which was a breakthrough in the area of magnetic levitation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, principles of magnetic levitation are being used successfully and broadly in different areas of technology and industries [3]. In 1997, Geim performed the diamagnetic levitation of a living organism (frog) in the air at the High Field Magnet Laboratory at Radboud University in Nijmegen, The Netherlands, which was a breakthrough in the area of magnetic levitation [4].…”
Section: Introductionmentioning
confidence: 99%
“…We will not review here the fundamentals and applications of this flow-free particle manipulation technique. Readers interested in this topic may refer to the recent review articles from Turker and Arslan-Yildiz [70], Gao et al [24], and Ge et al [71] for more details.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Aqueous solutions of simple paramagnet salts such as Mn(II) (e.g., MnCl 2 ) and Gd(III) (e.g., GdCl 3 ) are not compatible to biological applications [71]. In contrast, aqueous solutions of chelates of Mn(II) (e.g., Mn⋅EDTA) and Gd(III) (e.g., Gd⋅DTPA) become biocompatible [157,158].…”
Section: Particle Medium Exchangementioning
confidence: 99%
“…Recently, it was proposed that biological species (e.g., organelles, cells, virus, bacteria, etc.) can be separated using the Maglev system due to the differences in their densities . It was shown that specific diseases show characteristic changes in density for particular types of cells.…”
mentioning
confidence: 98%
“…can be separated using the Maglev system due to the differences in their densities. [3] It was shown that specific diseases show characteristic changes in density for particular types of cells. Tasoglu and co-workers reported a portable and self-contained device offering a great potential for rapid and on site sample analysis such as white blood cell cytometry.…”
mentioning
confidence: 99%